History of Islamic Culture Learning In Schools and Madrasah - Alfriani, Ranti Dwi; Hadi, Ihsan; Nafian, Zidni Ilman; Putri, Lara Agnesta (Suluah Pasaman, 2024)
Learning in madrasas is a religious subject that every student must take. learning can be achieved through guidance, teaching, practice and habituation activities. In the process of achieving these goals, a teacher must prepare learning materials or materials called media teaching materials, methods and learning evaluation. systematically and integrated teaching materials will be easily accepted by students so that the meaning of the teaching materials will be understood by students. Apart from that, other supporting facilities are also needed, namely technology. In terms of using learning media, you must pay attention to 4 stages, including preparation, presentation, application and continuation. Knowledge about teaching methods is very necessary for educators, because whether students learn successfully or not really depends on whether or not the teaching methods used by the teacher are appropriate. There are various kinds of learning methods that can be used by teachers in all subjects, one of which is the subject of Islamic Cultural History. The methods that can be used in subjects are the lecture method, question and answer method, discussion method, scramble method, debate method, demonstration method, timeline method, concept map method, role playing method, active knowledge sharing method. Meanwhile, for media, one of the characteristics of learning media is that it contains and carries messages or information to recipients, in this case meaning students. Some media can process messages and student responses so that media are often called interactive media.